Chlorophyll index, photochemical reflectance index and chlorophyll fluorescence measurements of rice leaves supplied with different N levels - Shrestha, Suchit; Brueck, Holger; Asch, Folkard (Journal of photochemistry and photobiology. B, Biology, 2012)
► Diagnosis of plant N status is required to optimise N fertilizer management. ► N-supply effects on SPAD and PRI values differentiation between N levels. ► The fraction of light utilised in photochemistry is not affect by N levels. ► Non-photochemical quenching is significantly affected by N levels. ► Non-photochemical quenching correlates with SPAD and PRI. Rapid and non-destructive diagnosis of plant N status is highly required in order to optimise N fertilizer management and use-efficiency. Additionally to handheld devices for measurements of chlorophyll indices (e.g., SPAD meter) parameters of canopy reflectance via remote sensing approaches are intensively investigated and the photochemical reflectance index (PRI) appears to be a reliable indicator for changes of the epoxidation state of xanthophyll cycle pigments. In order to assess the suitability of a handheld PRI as an additional tool for N diagnosis, rice plants were grown in a nutrient solution experiment with seven N-supply levels (0.18–5.71mM) and CI (SPAD) and PRI values and chlorophyll fluorescence parameters measured 20 and 28days after onset of treatments. N-supply had effects on both CI (SPAD) and PRI values with a more reliable differentiation between levels. Maximum quantum yield of PSII (Fv/Fm), actual efficiency of PSII photochemistry (ФPSII) and regulated non-photochemical quenching (ФNPQ) did not differ significantly between N levels. Non-photochemical quenching (NPQ) and fast- relaxing NPQ (NPQF) were significantly affected by N-supply. NPQ and NPQF, but not the slow-relaxing component (NPQS), were correlated with CI (SPAD) and PRI values. This finding which has not been reported for N-supply effects so far is indirect evidence that low N-supply induced xanthophyll cycle activity and that PRI values are able to indicate this at least in plants subject to severe N deficiency.